ANALISIS PENGARUH PENDAPATAN ASLI DAERAH (PAD) DAN BELANJA DAERAH (BD) TERHADAP INVESTASI DI KALIMANTAN BARAT - B21107049, AGUS SETIADI (Jurnal Pembangunan dan Pemerataan, 2016)
The purpose of this study was to determine the pattern of growth of gross regional domestic product (GRDP) sectoral West Kalimantan and to determine how the pattern of contributions and employment on sectoral GDP. The method used in this research is descriptive method, which describes the circumstances and events based on facts and data available in the province of West Kalimantan. Analysis using Eviews, Line Chart, and analysis of the Times Series, with the use of secondary data the provincial level. Secondary data Quantitative regional gross domestic product at current prices and official news entirely statistics obtained from Statistics province of West Kalimantan. In this study also uses qualitative data that includes a description of the data relevant to the study. The results showed that there are three main sectors that dominate the sector in the overall GDP sectoral West Kalimantan, namely agriculture, trade, and industrial sectors. Judging from the pattern of growth, the contribution pattern and the pattern of employment in regional gross domestic product by sector, the agricultural sector is a sector that is superior to the three main sectors, this indicates that the agriculture sector can be a mainstay in supporting the local economy, and two other key sectors is the sector has the potential to be developed. Based on the above results it can be deduced that the regional gross domestic product (GDP) of West Kalimantan sector is dominated by three main sectors in which the agricultural sector as the leading sectors, while other sectors are potential sectors and the need for substantive development by the government so as to encourage increased individual productivity each sector can then make a positive contribution to the local economy and will lead to the welfare of society.